Genuskoder i medeltida altarskåp - Liepe, Lena (Hikuin, 1999)
Gender Codes in Medieval Reredoses By Lena Liepe The issue of this article is the representation of female vs. male figures in the late medieval reredoses in Scania in medieval Denmark, and in North-Norway. The main purpose of the paper is to suggest outlines for a study of a medieval material from a genderdefined perspective. In this context, images are seen as carriers of meaning that participate in the shaping of a wider social and cultural context. The ordering of the church imagery during the Middle Ages, in point of formal properties as well as iconography, has produced and re-produced attitudes towards the sexes that can be analysed in terms of gender specific, or rather gender specifying, codes. In this first draft for such a study, the proportions of female and male figures respectively in the altogether 34 reredoses are accounted for, and questions are raised concerning how to analyse the representation, both as regards quantity and quality, in terms of the construction of medieval femininity and masculinity.